2008
DOI: 10.3748/wjg.14.1646
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer: Animal studies on the risk of hypoacidity and hypergastrinemia

Abstract: Gastric hypoacidity and hypergastrinaemia are seen in several conditions associated with an increased risk of gastric malignancy. Hypoacidity and hypergastrinaemia are closely related and their long-term effects are difficult to study separately in patients. Studies using animal models can provide valuable information about risk factors and mechanisms in gastric cancer development as the models allow a high degree of intervention when introducing or eliminating factors possibly affecting carcinogenesis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 72 publications
0
20
0
2
Order By: Relevance
“…H. pylori infection is an important independent risk factor for gastric carcinogenesis. It has been confirmed that H. pylori infection can result in hypergastrinemia [14]. Asymptomatic patients with H. pylori colonization have elevated serum gastrin concentrations [15], and following the eradication of H. pylori, there is a reduction of serum gastrin concentration in fasting patients [16].…”
Section: Discussionmentioning
confidence: 97%
“…H. pylori infection is an important independent risk factor for gastric carcinogenesis. It has been confirmed that H. pylori infection can result in hypergastrinemia [14]. Asymptomatic patients with H. pylori colonization have elevated serum gastrin concentrations [15], and following the eradication of H. pylori, there is a reduction of serum gastrin concentration in fasting patients [16].…”
Section: Discussionmentioning
confidence: 97%
“…Hypergastrinemia has been proposed in many models of gastric carcinogenesis and seems to be a common causative factor in otherwise different circumstances; in all species where long-term hypergastrinemia has been induced, an increased risk of gastric malignancy, with adenocarcinoma phenotype and even the signet-ring cells phenotype, was observed [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Achlorhydric gastritis or drug-induced inhibition of acid secretion increases the secretion of gastrin due to abolition of the negative feedback regulation [1]. Accordingly, long-term use of proton pump inhibitors has raised concerns about the ensuing hypergastrinemia [1][2][3], because hypergastrinemia increases the risk of gastric carcinogenesis in animal models [4,5]. Also cell line studies have implicated gastrin as a growth factor in gastric cancer cells [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 97%